A Suppressor of Tension or Judge or Official: The Peace Arbitrator in a Post-Serfdom Village - Bairašauskaitė, Tamara (Lietuvos istorijos studijos, 2023)
The article examines how the modern position of the peace arbitrator, the idea of which was borrowed from the ‘court of arbitration’ functioning in the Western world, emerged and was used in the governance structure of the Russian Empire. It reveals the role of the peace arbitrator in the administration and transformation of the post-serfdom village in the governorates of Vilnius, Kaunas, and Hrodna. The following stages in the activities of peace arbitrators are distinguished: (1) 1861–1862, when local landowners chosen as peace arbitrators managed the post-serfdom village, and (2) the time after the 1863–1864 uprising, when attempts were made to turn the Russian peace arbitrators, who had replaced the landowners in this role, into a tool of the Russification of the village. The analysis reveals the independence of the activities of peace arbitrators, which used to cause conflicts with the governorate authorities, police, and military structures.